Carbon Emissions With Forest Cover Change and Wood Harvest in the Dry Temperate Region of Pakistan Between 1908 and 2015 - Ahmad, Adnan; Ahmad, Shahid; Nabi, Ghulam; Zeb, Alam; Rajpar, Muhammad Nawaz; Ullah, Sami; Khalid, Faisal; Rahman, Mujibur; Liu, Qijing; Zu, Kuiling; Guo, Xinle; Wanghe, Kunyuan (Frontiers in Environmental Science, 2022)
Regional carbon emissions related to forest cover change (FCC) and wood harvest (WH) are critical for the accurate estimates of global carbon balance over an extended time period. Using remote sensing and inventory data, this study provides a comprehensive record of FCC, WH, and their integrated carbon emissions between 1908 and 2015 in the dry temperate regions of Pakistan. Results demonstrate a significant decline in forest area (21034 ha) at an annual rate of 0.56% from 1973 to 2015. The total WH was 24.84 million m3 (0.23 million m3 yr-1) between 1908 and 2015. Deforestation was responsible for a net loss of 1.39 million Mg C (0.018 million Mg C yr-1), while WH-related carbon emissions accounted for 11.29 million Mg C (0.52 million Mg C yr-1). The present results indicate that under the existing FCC and WH harvest scenario, the forests are acting as a net source of 0.29 million Mg C yr-1. Agriculture expansion and the heavy dependency of local communities on the forest’s resources, exclusion of conservation and local communities from forest management, insufficient monitoring, and weak law-enforcement were the striking drivers of FCC, WH, and their related emissions. These findings suggest that to maintain forest carbon and meet the communities’ requirements, counter approaches such as agriculture incentives, agroforestry, trophy hunting, alternative energy sources, and inclusion of conservation and secure community-based management are needed.